Dianthus somanus (Caryophyllaceae), a new species from Turkey - Oskay Di̇lek (Phytotaxa, 2018)
Dianthus somanus sp. nov. (Caryophyllaceae) is described as a new species from Kocasivri Mt. (Manisa), W-Anatolia (Turkey). Diagnostic characters, description and detailed illustration on the species are given, as well as a morphological comparison with the similar species D. goekayi, and D. erinaceus s.lat. (var. erinaceus, and var. alpinus). Habitat, distribution and conservation status of the new species are also provided.